Pengaruh Fitur Paylater, Spinjam dan Affiliate terhadap Minat Konsumen dalam Berbelanja pada Aplikasi Shopee : Studi Kasus Pengguna Shopee pada Mahasiswa FEBI UIN SATU Tulungagung - Tsani Syafiq Nuruddin, Syahru; Himmati, Risdiana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
Shopee is one of the largest marketplaces in Indonesia that provides several payment features, such as Shopee Paylater, Spinjam and Affiliate.This feature is also used to attract shopping interest for Shopee users without worrying that there is no cost to buy something. The existence of several payment features in the shopee application makes it easier for consumers to shop for whatever items they want. PThis study aims to determine the effect of featuresShopee PayLater, Spinjam and Affiliate for consumers who make transactions on the Shopee marketplace. This research focuses on students of the Faculty of Economics and Islamic Business, Sayyid Ali Rahmatullah Tulungagung State Islamic University who have accounts and are registered as Shopee PayLater, Spinjam and Affiliate. The method used in this research is qualitative methodwith a case study approach that uses source triangulation as the main data with in-depth interviews as well as observation and documentation as additional data. The results of this study indicate that these three features are the main choices for consumers for transactions. Based on data and analysis, Shopee PayLater is used as micro business capital, Spinjam is used for personal needs, and Affiliates tend to be used to earn income through marketing creative content products that include links uploaded on social media.